The hydroxypropyl–β-cyclodextrin complexation of toltrazuril for enhancing bioavailability - Zhang L; Liu MX; Lu CC; Ren DD; Fan GQ; Liu C; Liu MJ; Shu G; Peng GN; Yuan ZX; Zhong ZJ; Zhang W; et al. (Dove Medical Press, 2018)
Li Zhang,1,2,* Mengxi Liu,1,* Chaocheng Lu,1 Dandan Ren,1 Guoqing Fan,1 Chang Liu,1 Mengjiao Liu,1 Gang Shu,1 Guangneng Peng,1 Zhixiang Yuan,1 Zhijun Zhong,1 Wei Zhang,1 Hualin Fu1 1Department of Pharmacy, College of Veterinary Medicine, Sichuan Agricultural University, Chengdu, Sichuan, China; 2Institute of Traditional Chinese Medicine Pharmacology and Toxicology, Sichuan Academy of Chinese Medicine Sciences, Chengdu, Sichuan, China *These authors contributed equally to this work Introduction: Toltrazuril (Tol) is used to prevent and combat coccidiosis. However, its low aqueous solubility and poor oral bioavailability limit clinical application. Methods: To overcome the shortcomings, toltrazuril–hydroxypropyl–β-cyclodextrin inclusion complex (Tol-HP-β-CD) was prepared and characterized. The comparative plasma disposition kinetics of Tol was analyzed after a single orally administered dose of 10 mg/kg Tol or Tol-HP-β-CD in rabbits. Solution-stirring method was selected to prepare the inclusion complex. Complex formation was characterized by thin-layer chromatography, Fourier transform infrared spectrophotometry, and 1H nuclear magnetic resonance spectroscopy. In plasma profile, plasma samples were collected between 1 and 10 days following administration. Plasma Tol concentrations were determined by high-performance liquid chromatography. Results: In rabbit plasma, the time to peak concentration (Tmax) of Tol-HP-β-CD was shorter than that of Tol (12 h vs 24 h). Cmax (19.92±1.02 µg/mL) and area under the concentration–time curve (AUC0-∞, 1,176.86±70.26 mg/L h) of the Tol-HP-β-CD group significantly increased (p<0.01) than those of the Tol group (Cmax, 8.02±1.04 µg/mL; AUC0-∞, 514.03±66.65 mg/L h). Conclusion: It can be concluded that the Tol-HP-β-CD increased the aqueous solubility and enhanced the oral bioavailability in rabbits. Complexation with HP-β-CD is a feasible way to prepare a rapidly absorbed and more bioavailable Tol oral product. Keywords: toltrazuril, coccidian, hydroxypropyl–β-cyclodextrin, inclusion complex, pharmacokinetics